The definitive guide to blockchain for accounting and business : understanding the revolutionary technology - Dutta, Saurav K. (Bingley, U.K. : Emerald Publishing Limited, 2020)
Blockchain: a disruptive technology, or a new chance for the business world? The answer is both. With potential to change how economic transactions are recorded, stored, and verified, blockchain is changing the very face of the accounting industry. Despite its ramifications, business students of today and the practicing accountants of tomorrow are not being adequately trained in this new technology, due to a lack of resources exploring it from an accountant and business expert's perspective. Through its discussion of real-world and 'use-cases' The Definitive Guide to Blockchain for Business and Accounting distils an abstract technology into relatable experiences for business professionals. Including chapters from practicing professionals in the blockchain industry, The Definitive Guide shows readers how this innovative technology is changing the fundamentals of the business world. With international subject matter experts, this exciting new book includes perspectives from accountants, auditors, CEOs and CTOs on how blockchain is rewriting the future of the business and accounting world.
Chapter 1: Introduction / Saurav Dutta -- Chapter 2: Infrastructure supporting bitcoin blockchain / Saurav Dutta -- Chapter 3: Basic primer on blockchain terminology / Saurav Dutta -- Chapter 4: The consensus mechanism / Saurav Dutta -- Chapter 5: Smart contracts / Saurav Dutta -- Chapter 6: Tokenization / Saurav Dutta -- Chapter 7: A framework to evaluate blockchain use-cases / Phillip G. Bradford and Roger M. Benites -- Chapter 8: Financing corporate expansion through tokenization / Mike Rogers -- Chapter 9: A transparent new world : ethically sourced mineral supply chain / Nathan Williams and David Lee Williams -- Chapter 10: Tokenization of the Japanese real estate market / Mike Rogers -- Chapter 11: Blockchain-supported business innovations / Saurav Dutta -- Chapter 12: Internal controls / Gerard Brennan -- Chapter 13: Future directions / Saurav Dutta.
Includes bibliographical references and index.
Print version record.
Keywords: Blockchains (Databases); Finance -- Technological innovations; Accounting -- Data processing; Accounting -- Computer programs; Computers, Blockchain; Databases